Empty Time as Traumatic Duration: Towards a Cinematic Aevum. Issue 2 (June 2020) - Fuery, Kelli
Abstract : Frank Kermode uses the term aevum to question the links between origin, order, and time, associating experience with spatial form. Without end or beginning, aevum identifies an intersubjective order of time where we participate in the "relation between the fictions by which we order our world and the increasing complexity of what we take to be the 'real' history of that world"; being "in-between" time is a primary quality of the aevum . Regarding cinema, aevum identifies this third duration as emotional experience, occuring as traumatic time. It facilitates thinking beyond lived temporal experience of everyday life to a philosophy of experience that accounts for alternative sensoria of time, similar to the traumatic encounter. The cinematic aevum is equally not of the material, corporeal world; concurrently associating human reality with the myths of the human condition. To say that a cinematic aevum exists following traumatic scenes, is to specify a visual "time-fiction" in film, to recognise a spatial form that belongs neither to the finite time of the film's narrative, or of the "eternal" time outside the film's diegesis, but participates in the order (and linking) of both. Wilfred Bion's psychoanalytic works are used to discuss the traumatic symptom of "empty time": the inability to recollect, to make links between memory and experience, demonstrating a version of empty time that works as an external violence to spectator perception. Bion's theories offer fresh psychoanalytic perspective on trauma and its relationship to time by challenging classical ways of thinking about inner and outer perception.